The effect of multidrug exposure on neurological manifestations in carbamazepine intoxication: a nested case-control study - Ayala Hirsch; Maor Wanounou; Amichai Perlman; Bruria Hirsh-Raccah; Mordechai Muszkat (BMC, 2020)
Abstract Background In acute intoxication, carbamazepine concentration above 40 mcg/ml is associated with a risk of severe neurological consequences, including depressed consciousness, respiratory depression, cardiac conduction disorders, seizures, and death. Carbamazepine intoxication is often associated with the use of concomitant medications. However, the effect of exposure to other central-nervous-system (CNS) acting medications on the neurological manifestations of carbamazepine toxicity has not been evaluated. Objective To examine the effect of exposure to CNS-acting medications on the neurological effects of carbamazepine toxicity. Methods A retrospective nested case-control study of all patients > 18 years of age, with at least one test of carbamazepine levels > 18 mcg/ml recorded at the Hadassah Hospital Central Laboratory, between the years 2004-2016. Sociodemographic and clinical data were collected from the computerized medical records, and the characteristics of patients with and without severe neurological symptoms of carbamazepine intoxication were compared. Results Eighty patients were identified. In bivariate analyses, the odds of severe neurological symptoms was higher in patients with antidepressants use (odds ratio 8.7, 95% confidence interval: 1.8-41.2, p = 0.007), benzodiazepines use (8.6, 2.0-37.1, p = 0.004), and carbamazepine concentration above 30 mcg/ml (8.1, 1.9-33.3, p = 0.004). Multivariate models demonstrated that antidepressants and benzodiazepines were associated with severe neurological manifestations during carbamazepine intoxication, independently of carbamazepine concentration over 30 mcg/ml. ICU admission was associated in multivariate analysis with antidepressants (but not benzodiazepines) use, and with carbamazepine levels > 30 mcg/ml. Conclusions Among patients with carbamazepine intoxication, severe neurological symptoms are associated with exposure to benzodiazepines or antidepressants and with carbamazepine levels higher than 30 mcg/ml.